Arbuscular mycorrhizal fungi enhance active ingredients of medicinal plants: a quantitative analysis - Yuan, Ming-Li; Zhang, Meng-Han; Shi, Zhao-Yong; Yang, Shuang; Zhang, Meng-Ge; Wang, Zhen; Wu, Shan-Wei; Gao, Jia-Kai (Frontiers in Plant Science, 2023)
Medicinal plants are invaluable resources for mankind and play a crucial role in combating diseases. Arbuscular mycorrhizal fungi (AMF) are widely recognized for enhancing the production of medicinal active ingredients in medicinal plants. However, there is still a lack of comprehensive understanding regarding the quantitative effects of AMF on the accumulation of medicinal active ingredients. Here we conducted a comprehensive global analysis using 233 paired observations to investigate the impact of AMF inoculation on the accumulation of medicinal active ingredients. This study revealed that AMF inoculation significantly increased the contents of medicinal active ingredients by 27%, with a particularly notable enhancement observed in flavonoids (68%) and terpenoids (53%). Furthermore, the response of medicinal active ingredients in belowground organs (32%) to AMF was more pronounced than that in aboveground organs (18%). Notably, the AMF genus Rhizophagus exhibited the strongest effect in improving the contents of medicinal active ingredients, resulting in an increase of over 50% in both aboveground and belowground organs. Additionally, the promotion of medicinal active ingredients by AMF was attributed to improvements in physiological factors, such as chlorophyll, stomatal conductance and net photosynthetic rate. Collectively, this research substantially advanced our comprehension of the pivotal role of AMF in improving the medicinal active ingredients of plants and provided valuable insights into the potential mechanisms driving these enhancements.